Correctness of Dorodnitsyn's Method for Approximate Calculation of Eigenvalues in a Class of Boundary Value Problems - Sadovnichii, V. A.; Dubrovskii, V. V.; Maleko, E. M.; Popov, A. Yu (Differential equations, 2002)
(ProQuest: Abstract omitted; see image)[PUBLICATION ABSTRACT]